Learning by explaining orally or in written form? Text complexity matters. (August 2020) - Jacob, Leonie; Lachner, Andreas; Scheiter, Katharina
Abstract: In this experiment, we examined whether linguistic text complexity affects effects of explaining modality on students' learning. Students ( N = 115) read a high-complex and a low-complex text. Additionally, they generated a written or an oral explanation to a fictious peer. A control group of students retrieved the content. For the low-complex text, we found no significant differences between conditions. For the high-complex text, oral explaining yielded better comprehension than writing explanations. The retrieval condition showed the lowest performance. Mediation analyses revealed that the effect of explaining modality while learning from the high-complex text was mediated by the personal references and the comprehensiveness of the generated explanations. Our findings suggest that the effect of explaining modality emerges when students are required to learn from difficult texts. Furthermore, they show that oral explaining is effective as, likely due to increases of social presence, it triggers distinct generative processes during explaining. Highlights: Explaining modality (written vs. oral) showed to inconsistently affect learning. We tested whether explaining modality depends on text complexity. Oral explaining was best for high-complex, but not for low-complex texts. Personal references and the comprehensiveness of explanations were crucial for learning.